36. SOME FACTORS AFFECTING COMPLIANCE WITH LAW REGULATIONS ON PRIVATE MEDICAL EXAMINATION AND TREATMENT OF SPECIALIZED CLINICIANS IN SON LA CITY IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objectives: Analysis of some factors affecting compliance with regulations on private medicalexamination and treatment of specialized clinics in Son La city in 2023.Objective: Analyze some factors affecting compliance with regulations on private medicalexamination and treatment of specialized clinics in Son La city in 2023.Subjects and methods: Direct staff Participate in the management of the Medical OperationsDepartment and the Inspection Department under the Department of Health; Person in charge ofexpertise of the private medical examination and treatment of specialized clinics in Son La City.Conducted 04 in-depth interviews with 02 officers at the Medical and Pharmaceutical OperationsDepartment and the Inspection Department of the Health Department, 01 leader of Son La HealthDepartment and 01 Health Center leader of Son La city. Conducted 10 in-depth interviews with 10peope in charge of expertise of private medical examination and treatment of specialized clinics.Results: Some factors affecting the practice of natural conservation: Improving the knowledge andattitudes of person in charge of expertise has a positive influence on compliance with regulationsthrough training and propaganda for natural conservation practitioners. . Management, inspection andexamination have a positive impact on the implementation of legal regulations. Current legal documentsand instructions are not specific and have many inadequacies that cause difficulties for establishmentsand need to be corrected. The assignment of management to medical examination and treatment facilitiesis incomplete and lacks coordination. The health inspection force is too thin and lacks close attention,affecting management. Limited revenue from medical examination and treatment makes it difficult tomeet regulatory requirements. The consequences of the covid-19 epidemic have a negative impact onestablishments' compliance with legal regulations. The ongoing revision of the Law on MedicalExamination and Treatment is also a factor affecting compliance with the law.Conclusion: Raising awareness of practitioners through forms of communication, dissemination oflegal documents, etc. Advising on the development of documents, regulations and instructions on themanagement of private medical examination and treatment locality.
Keywords: Compliance, legal regulations, private medical examination and treatment, Son La city.